CONCEPT HISAB IN ISLAMIC ACCOUNTIZATION BASED ON ISLAMIC EPISTEMOLOGY ANALYSIS - Norazita Marina Abdul Aziz; Dr. Fadzila Azni Ahmad (Journal of Islamic, Social, Economics and Development, 2017)
Islamic accounting refers to calculations, reckoning and arrangements based onmuamalat affairs. The basis for Islamic accounting refers to a broad transaction covering alltransactions recording financial and non-financial transactions and calculating the balance ofreceipts, payments and profits that should be distributed to the persons entitled. To clarifyIslamic accounting profession in retrospect, it is necessary to first look at the foundations thatform the philosophy of Islam based on the core of Islamic philosophy that is epistemology.Based on Islamic theoretical knowledge, Islamic epistemology is aimed at the truth of theknowledge based on the pursuit of Allah obtained through the Quran, and the Hadith ie thewords, deeds and conversations of the Prophet (peace and blessings of Allaah be upon him)narrated from Sahih Sahih. The methodology of the study uses grounded theoretical studiesbased on the search for in-depth and detailed information. The scope of the study involves anin-depth examination of the major sources for the exploration of Islamic accounting relatedknowledge. Classification of concepts, categories, themes and patents is derived from groundedtheory analysis. The details and depth of information on Islamic accounting are formed toanswer the research questions. The findings of the study found that Islamic accounting is animportant basis in recording accounting related transactions and Islamic transactions such aszakat and waqf. Zakat and waqf accounting involves transactions to record basic proceduresbased on Islamic transactions. As such, Islamic accounting should be established through thecore of Islamic philosophy that involves Islamic tasawur, epistemology, ontology and Islamicaxiology. From a transparent study through the core of the Islamic philosophy, a form ofIslamic accounting concept has been established. The formation of Islamic accounting conceptswas formed through the principles, features and elements based on the core of Islamicphilosophy.